2022
DOI: 10.1021/acs.jced.2c00233
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Properties of Branched-Chain Amino Acids in Aqueous Solutions of 1-Dodecyl-3-methylimidazolium Bromide at Different Temperatures: Volumetric and Acoustic Measurements

Abstract: In terms of solute–solute and solute–solvent interactions, thermodynamic properties help characterize the structure and behavior of solutions. To identify the solute–solvent interactions, experimental density and speed of sound data at (288.15 K–318.15 K) at a 10 K interval have been measured for the aqueous mixtures of branched-chain acetyl substituted l-glycine and l-leucine with ILs. The measured data have been used to determine the apparent molar volume (V ϕ), the partial molar volume, and standard partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…We investigated the temperature sensitivity of ( V ϕ 0 ) through the application of the general polynomial equation utilized in our previous research Table outlines the constants ( a, b , and c ) specific to glycyl- l -alanine and glycyl- l -phenylalanine in an aqueous solution of [C 12 MIm] Br.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the temperature sensitivity of ( V ϕ 0 ) through the application of the general polynomial equation utilized in our previous research Table outlines the constants ( a, b , and c ) specific to glycyl- l -alanine and glycyl- l -phenylalanine in an aqueous solution of [C 12 MIm] Br.…”
Section: Resultsmentioning
confidence: 99%
“…They provide insightful information about the interactions between solutes and solvents throughout the solution phase. Understanding the interactions between solute and solvent molecules in mixtures is facilitated by focusing on two fundamental thermophysical properties: volume and compressibility. , Three imidazolium-based ILs, ranging from [C 6 mim]­[Br] to [C 10 mim]­[Br] to [C 12 mim]­[Br], were the subject of a thorough study of interactions that we carried out in our previous work. The results of these systems showed that the length of the alkyl chain in the IL affects both the volumetric and acoustic parameters. Notably, cations that were recognized as kosmotropes or structure-forming agents had alkyl chain lengths of n ( C ) = 6, 10, and 12.…”
Section: Introductionmentioning
confidence: 99%